The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1105/tpc.112.095885
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Decarboxylase Catalyzes the First Step of Quinolizidine Alkaloid Biosynthesis and Coevolved with Alkaloid Production in Leguminosae

Abstract: Lysine decarboxylase (LDC) catalyzes the first-step in the biosynthetic pathway of quinolizidine alkaloids (QAs), which form a distinct, large family of plant alkaloids. A cDNA of lysine/ornithine decarboxylase (L/ODC) was isolated by differential transcript screening in QA-producing and nonproducing cultivars of Lupinus angustifolius. We also obtained L/ODC cDNAs from four other QA-producing plants, Sophora flavescens, Echinosophora koreensis, Thermopsis chinensis, and Baptisia australis. These L/ODCs form a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(163 citation statements)
references
References 78 publications
7
152
0
Order By: Relevance
“…DFMO treatment alone decreased the PUT content in the leaves, and when applied in combination with Cd, it substantially lowered the root CAD and SPD contents of rice compared to Cd treatment alone. DFMO was also reported to inhibit the key enzyme of CAD synthesis, lysine decarboxylase, in Leguminosae [40]. Parallel with these changes, all the treatments increased the root PAO activity, while only treatments involving Cd (Cd, PUTpre+Cd or DFMO+Cd)…”
Section: Discussionmentioning
confidence: 78%
“…DFMO treatment alone decreased the PUT content in the leaves, and when applied in combination with Cd, it substantially lowered the root CAD and SPD contents of rice compared to Cd treatment alone. DFMO was also reported to inhibit the key enzyme of CAD synthesis, lysine decarboxylase, in Leguminosae [40]. Parallel with these changes, all the treatments increased the root PAO activity, while only treatments involving Cd (Cd, PUTpre+Cd or DFMO+Cd)…”
Section: Discussionmentioning
confidence: 78%
“…Recently, it has reported that LDCs isolated from leguminosae plants, which are involved in alkaloid biosynthesis, recognize both Lys and Orn (Bunsupa et al 2012), indicating that some LDC recognizes C5 (Lys) and C4 (Orn) as a substrate. In the analysis of PA contents in Arabidopsis plants after Cad treatment a peak for Cad but not for ApCad and DiApCad was detected, indicating that Arabidopsis SPDS does not recognize a C5 diamine, Cad, as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…1). Therefore, functional analyses on this diamine are very much limited (Gamarnik and Frydman 1991;Shevyakova et al 2000;Bunsupa et al 2012).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…1), destined for quinolizidine alkaloid biosynthesis (34). The enzyme responsible for lysine decarboxylation in quinolizidineproducing plants is an alanine racemase fold bifunctional lysine/ornithine decarboxylase (L/ODC) that has coevolved with alkaloid production in leguminous plants (35). This bifunctional L/ODC has evolved independently in plants from ODC, and has acquired a chloroplast-targeting sequence to localize it in the plastid where lysine is produced (35).…”
Section: Biosynthetic Diversification Via Endosymbiotic and Horizontamentioning
confidence: 99%